2023
DOI: 10.3390/systems11040172
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Digital Capabilities on Digital Transformation: The Mediating Role of Digital Citizenship

Abstract: The imperative of changes associated with digital transformation gave impetus to this study, which aims to examine the impact of digital capabilities and digital citizenship on digital transformation, as well as to identify the role of digital citizenship in the relationship between digital capabilities and digital transformation. Digital transformation is observed via change management and risk management, and two facets of digital citizenship are examined: information and data literacy and information securi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…DL is the ability and knowledge to apply digital technologies efficiently and is the basis for DGR and transformation. The higher the digital literacy of the management and employees, the more ready they are to execute and adjust to DGT [108]. DGT is the incorporation of digital technologies into all aspects of a business, radically altering how they operate and provide value to customers.…”
Section: Digital Readiness As a Mediatormentioning
confidence: 99%
“…DL is the ability and knowledge to apply digital technologies efficiently and is the basis for DGR and transformation. The higher the digital literacy of the management and employees, the more ready they are to execute and adjust to DGT [108]. DGT is the incorporation of digital technologies into all aspects of a business, radically altering how they operate and provide value to customers.…”
Section: Digital Readiness As a Mediatormentioning
confidence: 99%
“…Thus, our research incorporates the social system and digital technology, while analyzing the social system's impact on digital transformation enablers. A previous study demonstrated that information and data literacy and information security management, as components of digital citizenship, have a positive effect on change management and risk management during digital transformation [60]. Thus, the assumption was made that digital citizenship can positively contribute to the organization's faster adoption of digital technology and the establishment of digital transformation enablers.…”
Section: The Conceptual Frameworkmentioning
confidence: 99%